The Morphological Processes of Noun Forming Derivational Affixes in Dickens’ A Christmas Carol - Indriyana Savitri, Ni Made (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p15, 2018)
This study entitled The Morphological Processes of Noun Forming Derivational Affixes in Dickens’ A Christmas Carol aims to analyze the word class of base forms and derivational affixes forming nouns used in a fiction novel. The data were taken from the novel entitled A Christmas Carol written by Charles Dickens in 1843 by applying documentation method and note-taking techniques. The technique of analyzing data was done by classifying the derivational affixes forming nouns according to type of affixes and reducing the words containing derivational affixes that were similar. The data were analyzed by applying the theory of how new words are formed as derivations in morphology by Katamba (1993) as the main theory and the theory by Bauer (1983) as the supporting one. The findings showed that there were t hree classes of the base form used to produce new noun-based lexeme in the data, namely verb, adjective and noun. Types of affixes that were used were only suffixes, namely suffix –al, -er, -ar, -or, -ing, -y, -ion, -ation, -ment, -ance, and –age which are attached to verb base, suffix –ity, -th, -ness, and –ence which are attached to adjective base and suffix –y which are attached to noun base.